Tin Oxide Modification of Indium Oxide Gas Sensitive Layers to Increase Efficiency of Gas Sensors - O. G. Reutskaya; S. V. Denisuk; A. M. Kudanovich; N. I. Mukhurov; I. A. Taratyn; V. G. Luhin (Приборы и методы измерений, 2023)
Monitoring of air pollutions is one of actual trends in the development of industrial and domestic instrumentation. There are sets of tasks for improving gas analytical instruments because of increasing demand for control of a concentration of explosive and toxic gases on a level with maximum allowable concentration. The aim of the paper was to investigate the methods of formation and elemental composition of indium oxide films modified with tin oxide on the surface of gas sensor elements as one of the promising compounds for improving the detection efficiency of explosive and toxic gases in the environment. The processes of formation of gas-sensitive films deposited on the surface of nichrome alloy information electrodes were studied in this article. Substrates of anodic aluminum oxide with area of 10 × 10 mm2 and a thickness of 45 ± 0,5 μm were chosen for research. Two layers on the surface of the samples were formed. The first layer was formed from NiCr alloy (Ni – 80 %, Cr – 20 %) with a thickness of ≈ 0.3 μm by ion-plasma sputtering. The second layer was based on indium oxide with addition of tin oxide with thicknesses from ≈ 0.3 μm to ≈ 1.0 µm and coated with sol-gel technology. Five samples of gas-sensitive films were formed with different methods of deposition and heat treatment. Scanning electron microscopy was used for study of films’ morphology and elemental compositions of samples. The most perfect continuous semiconductor films were obtained by multilayer applying of a sol-gel paste. When semiconductor films were processed at annealing temperatures of 700 °C and higher in vacuum so there was observed cracking of semiconductor films up to a layer of NiCr alloy. The developed surface of gas-sensitive films allows to reach high sensitivity and affectivity of semiconductor sensors for control of air gas composition.